Bone effects of canagliflozin, a sodium glucose co-transporter 2 inhibitor, in patients with type 2 diabetes mellitus. Issue 1 (2nd January 2017) - Blevins, Thomas C.; Farooki, Azeez
ABSTRACT: Canagliflozin, a sodium glucose co-transporter 2 (SGLT2) inhibitor approved for the treatment of type 2 diabetes mellitus (T2DM), lowers blood glucose by inhibiting renal glucose reabsorption and increasing urinary glucose excretion. It has been reported that SGLT2 inhibitors may have potential adverse effects on bone, including increased fracture risk and decreased bone mineral density (BMD). Across clinical studies, canagliflozin was not associated with meaningful changes in serum or urine calcium, vitamin D, or parathyroid hormone. Minimal increases in serum phosphate and magnesium that were within normal limits were seen with canagliflozin versus placebo. Canagliflozin was associated with increases in serum collagen type 1 beta-carboxy telopeptide (beta-CTX), a bone resorption marker, and osteocalcin, a bone formation marker. Decreases in total hip BMD were seen with canagliflozin 100 and 300 mg versus placebo after 2 years (–1.7%, –2.1%, –0.8%; differences of –0.9% and –1.2%), but not at other skeletal sites (normal age-related bone loss, ~0.5-1.0%/year). Changes in beta-CTX and total hip BMD were significantly associated with weight loss, which is known to increase bone resorption markers and decrease BMD. Canagliflozin was associated with a higher fracture incidence in an interim analysis of the CANagliflozin cardioVascular Assessment Study (CANVAS) in patients with a history or high risk of cardiovascular disease (incidence per 100 patient-years of 1.6, 1.6, and 1.1 with canagliflozin 100 and 300 mg and placebo), but not in other clinical studies of patients with T2DM. Fractures tended to occur as early as 12 weeks after initiating treatment and were primarily located in the distal parts of the upper and lower extremities. The reason for increased fracture risk with canagliflozin treatment is unknown, but is likely not related to a direct effect of canagliflozin on bone-related biomarkers. Data from ongoing canagliflozin studies, including CANVAS, will provide additional information on fracture risk in patients with T2DM.